Blue Economy : A Path for Krasnodar Krai - Damianova, Adriana (World Bank, Washington, DC, 2020)
The policy note focuses on the well-established coastal- and marine-based sectors, such as recreational tourism and fisheries, that make a significant contribution to the economy of Krasnodar Krai and where challenges and unsustainable patterns could undermine their growth ambitions and translate into missed economic opportunities. It also discusses the critical importance of protecting the coastal and marine ecosystem from marine litter as well as ways to preserve the substantial economic opportunities that could be derived from a healthier coastal and marine space. Information on pollution in the Black Sea that stems from other sources, such as untreated effluents and oil spills, is intentionally limited in order to expand the focus on plastic litter as a global and regional challenge that needs country-specific measures. The World Bank has recently launched the ‘Blueing the Black Sea’ (BBSEA) program aiming to reduce pollution in the Black Sea through a set of complementary activities that include a thorough analysis of the sea’s current contaminants. The BBSEA will support the Black Sea countries in the implementation of the Common Maritime Agenda (CMA) for prioritizing and catalyzing blue economy investments in the Black Sea basin. More specifically, the program aims to strengthen economic, technical, and communication tools to promote regional collaboration and private sector engagement in pollution prevention in the Black Sea. However, the ambition of the BBSEA is to progressively include all the Black Sea countries in this World Bank initiative beyond the initial four, Turkey, Georgia, Ukraine, and Moldova, through additional resources. For Krasnodar Krai, there are multiple opportunities for learning and knowledge exchange in the technical assistance format of the BBSEA that could help support the implementation of the specific recommendations in this policy note.